35th Nordic Ethnology and Folklore Conference in Reykjavik - Teidearu, Tenno (Estonian Literary Museum, the Estonian National Museum and the University of Tartu, 2023)
The 35th Nordic Ethnology and FolkloreConference, titled RE:22, was held from June 13thto 16th, 2022 was held in Reykjavik, Iceland.